Processing of Regular and Irregular Past‐Tense Verb Forms in First and Second Language Reading Acquisition. Issue 4 (17th September 2013) - de Zeeuw, Marlies; Schreuder, Rob; Verhoeven, Ludo
Abstract : We investigated written word identification of regular and irregular past‐tense verb forms by first (L1) and second language (L2) learners of Dutch in third and sixth grade. Using a lexical decision task, we measured speed and accuracy in the identification of regular and irregular past‐tense verb forms by children from Turkish‐speaking homes (L2 learners) and monolingual Dutch‐speaking homes (L1 learners). All beginning readers of Dutch had relatively more difficulties with the identification of irregular verb forms than regular verbs forms, but the effects were stronger for L2 learners than for L1 learners. These processing differences were only present in third grade, however, indicating that with increased target language experience, the reading of past‐tense verb forms becomes more fluent and automatized in both L1 and L2 learners.